Pengetahuan dan Sikap Guru PAUD terhadap Kesehatan Reproduksi Anak - Eska Riyanti; Yuli Mulyanti (Poltekkes Kemenkes Jakarta III, 2018)
Various phenomena that occur negative behavior are often seen in everyday life in children through newspapers or television found cases of early childhood such as violence whether physical, verbal, mental violence or even sexual abuse or violence has befall children. One important preventive measure is to provide adequate knowledge to parents and children of reproductive and sexual education, so that early childhood children will recognize the roles of their sex and sexual organs and be cautious about dangerous treatments that can be received, such as sexual harassment and violence sexual. Teachers as educators are required to be able to explain reproductive health to students even though they are still in kindergarten. The purpose of this study was to determine the effect of health education on knowledge and attitudes about reproductive health in ECD teachers. This research is a quantitative study with pre and post Quasi experimental designs. Population The target of this study was all PAUD teachers with a sample of 40 people. The data analysis method used is Paired T test. The results of the analysis show that there is an increase in the score of knowledge about reproductive health of early childhood to PAUD teachers of 1.075 at the value of t = 2.845 and p-value of 0.007. And an increase in the score of PAUD teacher attitudes towards reproductive health of early childhood is 1,800 at the value of t = 2.118 and p-value 0.041. Conclusion; significant influence of health education interventions on early childhood reproductive health in PAUD teachers